2008
DOI: 10.1073/pnas.0805500105
|View full text |Cite
|
Sign up to set email alerts
|

Dysfunction in ankyrin-B-dependent ion channel and transporter targeting causes human sinus node disease

Abstract: The identification of nearly a dozen ion channel genes involved in the genesis of human atrial and ventricular arrhythmias has been critical for the diagnosis and treatment of fatal cardiovascular diseases. In contrast, very little is known about the genetic and molecular mechanisms underlying human sinus node dysfunction (SND). Here, we report a genetic and molecular mechanism for human SND. We mapped two families with highly penetrant and severe SND to the human ANK2 (ankyrin-B/AnkB) locus. Mice heterozygous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
184
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 162 publications
(193 citation statements)
references
References 31 publications
9
184
0
Order By: Relevance
“…In addition, Ca v 1.3 −/− mice reproduce severe AV dysfunction typical of human congenital heart block (16). Previous studies demonstrated that Ca v 1.3-mediated I Ca,L plays a major role in the determination of heart rate and impulse conduction in mice and humans (10,11,14,16,17,19). However, despite the importance of Ca v 1.3-mediated I Ca,L in determining the rate of the diastolic depolarization in isolated SAN and AV node myocytes (14,16), it was unclear how Ca v 1.3 loss of function translates into SSS in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Ca v 1.3 −/− mice reproduce severe AV dysfunction typical of human congenital heart block (16). Previous studies demonstrated that Ca v 1.3-mediated I Ca,L plays a major role in the determination of heart rate and impulse conduction in mice and humans (10,11,14,16,17,19). However, despite the importance of Ca v 1.3-mediated I Ca,L in determining the rate of the diastolic depolarization in isolated SAN and AV node myocytes (14,16), it was unclear how Ca v 1.3 loss of function translates into SSS in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Affected individuals with SANDD present with profound deafness, bradycardia, and dysfunction of AV conduction (10). Mutation in ankyrin-B causes SSS by reduced membrane targeting of Ca v 1.3 channels (11). The relevance of Ca v 1.3 channels to SSS is demonstrated also by work on the pathophysiology of congenital heart block, where down-regulation of Ca v 1.3 channels by maternal Abs causes heart block in infants (12).…”
mentioning
confidence: 99%
“…Trafficking of ion channel proteins to the surface membrane involves a series of tightly regulated events coordinated by ER resident proteins, microtubules, transport vesicle and Golgi apparatus, the actin cytoskeleton, myosins, and anchoring proteins (2). The importance of correct ion channel trafficking is highlighted by a number of channel-linked genetic diseases whose defect is associated with failure to reach the cell surface (4)(5)(6)(7)(8).…”
mentioning
confidence: 99%
“…However, we now know that human disease, particularly excitable cell disease, may be caused by defects in non-ion channel polypeptides including in cellular components residing well beneath the plasma membrane. For example, over the past few years, a new class of potentially fatal cardiac arrhythmias has been linked with cytoplasmic proteins that include sub-membrane adapters such as ankyrin-B (ANK2) [1][2][3][4][5] , ankyrin-G (ANK3) [6][7][8] , and alpha-1 syntrophin [9] , membrane coat proteins including caveolin-3 (CAV3) [10] , signaling platforms including yotiao (AKAP9) [11,12] , and cardiac enzymes (GPD1L) [13] . The focus of this review is to detail the exciting role of lamins, yet another class of gene products that have provided elegant new insight into human disease.…”
Section: Introductionmentioning
confidence: 99%